PROSES RESERVASI PERJALANAN WISATA BERLAYAR MENUJU PULAUKOMODO MELALUI KAKABANTRIP TOUR AND TRAVEL SERVICE - Prakoso, Muhammad Noer; Pratiwi, Annisa (Journal of Indonesian Tourism and Policy Studies, 2017)
The focus of this study is to discuss (1) reservation process of sailing trip to Komodo Island (2) and to know what facilities, rights and obligations given Kakabantrip for tourists who follow sailing tour of komodo. Tourist Reservation Process conducted by Kakabantrip all of them aims to provide security and comfort to tourists. With the reservation process made by Kakabantrip who sending personal data of tourists, Kakabantrip can know the characteristics and needs of tourists so that the tourists can get the best service from Kakabantrip. The method used in the manufacture and writing of this Final assigmment is a descriptive method through the written or oral words of the people and the behavior observed. The author also uses the method of observation is through field work practices conducted by the author at Kakabantrip Tour And Travel Service.